Yang-deficiency constitution drives poor outcomes in clear cell renal cell carcinoma by modulating the tumour immune microenvironment - Kho, Boon Seng; Zhou, Zongyuan; Liu, Rui; Sui, Yihang; Zhang, Yingnan; Yao, Jiaqi; Lu, Huanhuan; Zhou, Guowei; Zhang, Bo; Wang, Yinyin (Frontiers in Immunology, 2025)
BackgroundClear cell renal cell carcinoma (ccRCC) is the most common subtype of kidney cancer, often diagnosed at advanced stages due to a lack of reliable early biomarkers. Recent studies suggest that the traditional Chinese medicine (TCM) body constitution, particularly the Yang-Deficiency Constitution (YDC), may influence tumour development by altering the immune microenvironment. However, the mechanistic connection between YDC and ccRCC prognosis remains largely unexplored.ObjectiveThis study aims to elucidate the impact of YDC on the immune landscape and clinical outcomes of ccRCC and to identify novel prognostic biomarkers and potential herbal therapeutic agents guided by YDC characteristics.MethodsWe integrated bulk transcriptomic data from 12 YDC-classified individuals and 530 ccRCC patients, alongside single-cell RNA-seq profiles from one PBMC and two ccRCC tumour samples. Through differential expression analysis, WGCNA, and machine learning-based survival modelling, we identified YDC-related biomarkers and assessed their immunological relevance using ESTIMATE, CIBERSORT, and CellChat. A gene expression-based scoring framework (GSVA) was developed to systematically prioritize 622 herbal ingredient perturbations for their potential survival benefits. Key ingredients were further validated through molecular docking and experimental assays.ResultsPatients with YDC-associated ccRCC exhibited poorer survival. Nine intersecting genes were screened and used to construct a prognostic model, whereby seven key biomarkers—MXD3, PLCB2, CCDC88B, DEF6, IFNG, TBC1D10C, and PLEKHN1—were significantly influenced the prognosis of renal cancer. These genes were found to modulate immune cell populations, particularly CD8+ T cells, Tregs, and M1 macrophages, with IFNG serving as a central regulatory hub. Baicalein was identified and validated as a promising therapeutic agent targeting IFNG.ConclusionThis study highlights the crucial role of YDC in shaping the immune microenvironment and influencing survival in ccRCC. By integrating constitution-based stratification, immune profiling, and herbal medicine screening, we offer a unique framework for biomarker discovery and propose baicalein as a potential YDC-targeted adjuvant therapy.